1982
DOI: 10.2307/3114630
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship in Public Enterprise: General Enrique Mosconi and the Argentine Petroleum Industry

Abstract: The economic history of Latin America offers an unusual paradox. For much of the twentieth century, nationalist governments have fostered the growth of state enterprise, but for the most part the proponents of such policies have received little attention. The Argentine petroleum industry is a case in point. While the state oil company Yacimientos Petrolíferos Fiscales (or YPF) grew from relatively modest origins into the largest firm in the country, its most important architect, General Enrique Mosconi, has re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…3 In earlier decades, scholars from a range of disciplines frequently drew attention to the military's involvement in the economy. The 1960s brought a first wave of studies, often by economic historians and historically minded economists, who identified the military as a key (and often admirable) protagonist in economic development and industrialization (Leff 1968;Baer 1969;Wirth 1970;Solberg 1979). In the 1970s and 1980s, a second wave of studies emphasized structural factors tying the military to the development of industry and the defense sector.…”
Section: Surveying the Scholarshipmentioning
confidence: 99%
“…3 In earlier decades, scholars from a range of disciplines frequently drew attention to the military's involvement in the economy. The 1960s brought a first wave of studies, often by economic historians and historically minded economists, who identified the military as a key (and often admirable) protagonist in economic development and industrialization (Leff 1968;Baer 1969;Wirth 1970;Solberg 1979). In the 1970s and 1980s, a second wave of studies emphasized structural factors tying the military to the development of industry and the defense sector.…”
Section: Surveying the Scholarshipmentioning
confidence: 99%
“…In 1907, oil was found in great amounts (Gadano, 2006) and the President at that time issued a decree that created a national oil reserve (Solberg, 1986). Three years after the discovery of oil, the world's first state-owned oil company was created (Solberg, 1982). Even so, for many years to come, the State did not commit the sufficient energy to develop this resource.…”
Section: Historical Narrative Of Oil Contracts In Argentinamentioning
confidence: 99%
“…Argentina became the first country outside the USSR to have a completely vertically integrated state-run oil company. Yacimientos Petrolíferos Fiscales, which was also known by the acronym YPF (Solberg, 1982), launched a strategic plan of investments aiming to cover all areas of the oil industry: production, exploration, refinement and distribution at competitive prices, and making it fully autonomous from the central government, with the exception of its annual budget and major purchases that required credit. Nevertheless, oil exploration lagged behind because the company did not have enough financial resources to put forward a large exploratory drilling plan (therefore, limited scale of production).…”
Section: Historical Narrative Of Oil Contracts In Argentinamentioning
confidence: 99%
See 2 more Smart Citations